2020
DOI: 10.1002/jsde.12429
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fine Bubbles on Removal of Linear Alkyl Benzene Sulfonate Surfactant during the Rinsing Stage of Laundry Washing

Abstract: The use of fine bubbles is a promising approach to remove surfactant efficiently during the rinsing process of clothing, to fulfill a requirement. Therefore, the influence of fine bubbles on the removal performance of surfactant from cloth during the rinse process of pulsator washing machine (top loading type) was investigated. The test apparatus was assembled by connecting a microbubble generation tank and a small washing machine with tubes and circulating fine bubble water to a small washing machine. Swatche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The manufacturers have explained in various ways that the produced submicron particles, i.e., UFBs, are effective in improving the cleaning efficiency [5]. Of course, these cleaning benefits are not only just guaranteed by the manufacturers through their testing but also supported by academic studies [6][7][8][9][10]. Successful applied research has also been reported in industrial processes such as flotation [11] and water treatment [12] as well as in agriculture [13] and fisheries [14].…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturers have explained in various ways that the produced submicron particles, i.e., UFBs, are effective in improving the cleaning efficiency [5]. Of course, these cleaning benefits are not only just guaranteed by the manufacturers through their testing but also supported by academic studies [6][7][8][9][10]. Successful applied research has also been reported in industrial processes such as flotation [11] and water treatment [12] as well as in agriculture [13] and fisheries [14].…”
Section: Introductionmentioning
confidence: 99%
“…"Fine bubbles" are defined by the International Organization for Standardization (ISO) as bubbles having diameters of less than 100 µm. Among fine bubbles, those with diameters of 1-100 µm are referred to as microbubbles (MiBs) [1][2][3]. MiBs have several special properties that include the following: (1) much slower rising velocity compared with macrobubbles (MaBs) (with diameters between 100 µm and 2 mm) [2,4]; (2) large ratio of contact surface area to bubble volume [5]; (3) high internal gas pressure [6][7][8]; (4) electrically charged bubble surface [7,9]; (5) tendency to shrink and eventually dissolve in water [4].…”
Section: Introductionmentioning
confidence: 99%
“…Joni et al [17] also reported that the application of MiBs in an aquaculture system increased the DO from 4.5 mg L −1 to 7.9 mg L −1 . In addition to their use in aquaculture facilities, MiBs have been used to improve the water quality of wastewater contaminated with various hazardous materials, such as azo dye [18], methylene blue [19], phenol [6,20], palm oil [8], diesel oil [21], trichloroethylene [22], surfactants [3], pesticides [23], and pathogenic bacteria [24]. MiBs have also been used to remove microalgal cells [25] and planktonic crustaceans [26].…”
Section: Introductionmentioning
confidence: 99%